Early diagnosis and survival outcomes in silicosis: a retrospective cohort study of 11,809 patients in Guangdong Province, China (1956–2020) - Fan, Chunyue; Wang, Yuhao; Chen, Jingjing; Wei, Qiaoli; Hu, Shijie; Xia, Lihua; Huang, Jiawen; Liang, Weihui; Wu, Lin; Li, Xudong (Frontiers in Public Health, 2025)
IntroductionSilicosis, a progressive occupational lung disease caused by silica dust exposure, remains a global public health challenge due to limited therapeutic options. Early diagnosis is hypothesized to improve survival outcomes, yet evidence linking diagnostic stage to mortality remains scarce. This study aimed to evaluate the association between early diagnosis and survival in silicosis patients and assess the impact of delayed diagnosis on mortality.MethodsA retrospective cohort study analyzed 11,809 silicosis patients diagnosed between 1956 and 2020 in Guangdong Province, China. Data were extracted from occupational disease registries, multi-sectoral databases, and provincial monitoring systems. Exclusion criteria included ambiguous diagnosis dates, pre-adolescent exposure, and missing variables. Cox proportional hazards models adjusted for covariates (sex, age, region, industry, exposure duration) were used to assess mortality risks across stages I–III. Survival curves, temporal trends, and subgroup analyses were performed.ResultsMost patients (77.8%) were diagnosed at stage I, with median survival times declining sharply across stages: 27 years (stage I), 20 years (stage II), and 11 years (stage III) (p < 0.001). Adjusted mortality risks increased progressively: stage II (HR = 1.42, 95%, CI: 1.33–1.51) and stage III (HR = 2.42, 95%, CI: 2.17–2.70)compared to stage I. Temporal analysis revealed peak diagnoses in 1963 and the early 1980s, stabilizing post-2006. Subgroup analyses confirmed staging as an independent prognostic factor across industries and exposure durations (p < 0.001).DiscussionThis study demonstrates that early diagnosis significantly prolongs survival in silicosis patients, with advanced stages correlating with exponentially higher mortality. The findings underscore the urgent need for systematic early screening, such as high-resolution CT, and stricter occupational health policies to reduce silica exposure. Despite limitations, including unmeasured confounders like smoking status, this research provides critical evidence to inform global strategies for mitigating silicosis through timely detection and workplace safety reforms.